NUMERICAL MODELING OF YEAR-ROUND CIRCULATION IN DEEP LAKES - Astrakhantsev G.P.; Rukhovets L.A.; Yegorova N.B. (My University, 1987)
This paper describes a three-dimensional discrete model of the annual climatic circulation of a deep, thermal-stratified lake. The laws of conservation of heat and mass are exactly satisfied in it, and morphometry is taken into account without making the bottom relief flat. As a boundary condition the heat flux is specified at the surface of the lake, making it possible to use the model for forecasting calculations in which the surface temperature cannot be specified.